The Land of the Silver Apples - Farmer, Nancy, 1941- (Atheneum Books for Young Readers, 2009)
After escaping from the Sea of Trolls, the apprentice bard Jack plunges into a new series of adventures, traveling underground to Elfland and uncovering the truth about his little sister Lucy.